Strategic Incorporation of Experiential Learning in Sustainability Through the Project “Path to A Sustainable Country” - Claudia Dulce; Andrea Díaz (Universitas Diponegoro, 2023)
Path to a Sustainable Country (in Spanish “Ruta País Sostenible”) is an institutional commitment that seeks to reinforce the importance of natural resources in the university community and promote learning based on experience. We make field trips around the country that connect nature and communities. The areas selected are the National Natural Parks (NNP) and the protected areas of Colombia (12% of the country's territory). This project has the intention to be closer to the territory´s realities. At the same time, we have an experiential analysis to develop academic projects that promote the conservation of ecosystem services, and the improvement of the quality of life of the surrounding communities. Since 2022, we have made three field trips to the NNP: Chingaza (paramo), Bahía Málaga (mangrove), Desierto de la Tatacoa (tropical dry forest), El Zoque (andean forest), El Cocuy (Glacier). On those trips, we have had 150 participants among students, professors, staff, and alumni. We tested the most appropriate and effective sustainable learning process. The result indicated that 50% of people memorize the concepts when they directly observe nature and communities. Meanwhile, the second most successful tool was applied research (20%), followed by classes (16%), and finally, laboratory practices (14%).